Cellular ROS and Antioxidants: Physiological and Pathological Role - Andrey V. Kozlov; Sabzali Javadov; Natascha Sommer (MDPI AG, 2024)
Reactive oxygen species (ROS) are highly reactive oxygen derivatives that include free radicals such as superoxide anion radical (O2•−) and hydroxyl radical (HO•), as well as non-radical molecules hydrogen peroxide (H2O2), peroxynitrite (ONOO−), and hypochlorous acid (HOCl) [...]